An Activatable Near‐Infrared Afterglow Theranostic Prodrug with Self‐Sustainable Magnification Effect of Immunogenic Cell Death. Issue 40 (25th August 2022) - Gao, Zhiyuan; Jia, Shaorui; Ou, Hanlin; Hong, Yuning; Shan, Ke; Kong, Xianglong; Wang, Zhiming; Feng, Guangxue; Ding, Dan
Abstract: Herein, we report an activatable near‐infrared (NIR) afterglow theranostic prodrug that circumvents high background noise interference caused by external light excitation. The prodrug can release hydroxycamptothecin (HCPT) in response to the high intratumoral peroxynitrite level associated with immunogenic cell death (ICD), and synchronously activate afterglow signal to monitor the drug release process and cold‐to‐hot tumor transformation. The prodrug itself is an ICD inducer achieved by photodynamic therapy (PDT). PDT initiates ICD and recruits first‐arrived neutrophils to secrete peroxynitrite to trigger HCPT release. Intriguingly, we demonstrate that HCPT can significantly amplify PDT‐mediated ICD process. The prodrug thus shows a self‐sustainable ICD magnification effect by establishing an "ICD‐HCPT release‐amplified ICD" cycling loop. In vivo studies demonstrate that the prodrug can eradicate existing tumors and prevent further tumor recurrence through antitumor immune response. Abstract : We report a theranostic prodrug that could self‐report the drug release, immunogenic cell death (ICD) progression, and cold‐to‐hot tumor transformation with activated near‐infrared afterglow chemiluminescence. Such an intelligent prodrug also shows a unique self‐sustainable ICD magnification effect, completely eradicating the existing tumor and preventing further tumor recurrence through enhanced antitumor immune response.